The differences of fibrinogen levels in various types of hemorrhagic transformations - Long, Jingfang; Chen, Jiahao; Huang, Guiqian; Chen, Zhen; Zhang, Heyu; Zhang, Ye; Duan, Qi; Wu, Beilan; He, Jincai (Frontiers in Neurology, 2024)
Introduction Hemorrhagic transformation (HT) is a serious complication that can occur spontaneously after an acute ischemic stroke (AIS) or after a thrombolytic/mechanical thrombectomy. Our study aims to explore the potential correlations between fibrinogen levels and the occurrence of spontaneous HT (sHT) and HT after mechanical thrombectomy (tHT). Methods A total of 423 consecutive AIS patients diagnosed HT who did not undergone thrombolysis and 423 age- and sex-matched patients without HT (non-HT) were enrolled. Fibrinogen levels were measured within 24 h of admission after stroke. The cohorts were trisected according to fibrinogen levels. The HT were further categorized into hemorrhagic infarction (HI) or parenchymal hematoma (PH) based on their imaging characteristics. Results In sHT cohort, fibrinogen levels were higher in HT patients than non-HT patients (p < 0.001 versus p = 0.002). High fibrinogen levels were associated with the severity of HT. HT patients without atrial fibrillation (AF) had higher levels of fibrinogen compared to non-HT (median 3.805 vs. 3.160, p < 0.001). This relationship did not differ among AF patients. In tHT cohort, fibrinogen levels were lower in HT patients than non-HT patients (p = 0.002). Lower fibrinogen levels were associated with the severity of HT (p = 0.004). The highest trisection of fibrinogen both in two cohorts were associated with HT [sHT cohort: OR = 2.515 (1.339–4.725), p = 0.016; that cohort: OR = 0.238 (0.108–0.523), p = 0.003]. Conclusion Our study suggests that lower fibrinogen level in sHT without AF and higher fibrinogen level in tHT are associated with more severe HT.